Effect of education on monetary poverty in the regions of Peru - Arias, Luis (2019)
The objective of this research was to analyze the effect of education on monetary poverty in the regions of Peru. As a source of information, the SIRTOD database of the National Institute of Statistics and Informatics was used for the period 2007 to 2016. The study is based on the framework of human capital theory and consumer microeconomic theory. Therefore, the study is considered as hypothetico-deductive. Education was approached through the percentage of the economically active population by educational levels; primary, secondary, non-university education and university education, and poverty by the percentage of the population that have less expenditure than the monetary poverty line. The main hypothesis of the study is that the higher level of education has a positive effect in the reduction of monetary poverty, through the mechanism of productivity and income improvement. The estimation methodology was the panel data model; fixed and random effects. The research results show that from the beginning of secondary education monetary poverty is reduced in the regions of Peru; that is, the population educated by educational levels increases by 10%, this would lead to a reduction of poverty in the regions by 1.07%, 1.68% and 0.83% respectively. Finally, public policy is that the regions and the central government close gaps in access to education, especially in secondary education and non-university education, which have the greatest effect.